2001
DOI: 10.1046/j.1432-1327.2001.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the rat adrenal zona fasciculata/reticularis specific protein, inner zone antigen (IZAg), as the putative membrane progesterone receptor

Abstract: Using immunological methods, a protein specific to the inner zones of the rat adrenal cortex, and called inner zone antigen (IZAg), was previously shown to have two interrelated forms of 26 kDa (IZAg1) and 55±60 kDa (IZAg2), and to have an action on steroid hydroxylation. After twodimensional gel electrophoresis, and immunoaffinity column purification, N-terminal amino-acid analysis showed that the first 12 amino acids were identical to those of a recently described putative membrane located progesterone recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 37 publications
(52 reference statements)
0
53
0
Order By: Relevance
“…As shown in Fig. 5, rIZA1 was distributed diffusely in the cell, forming vesicular structures, suggesting its association with the membrane compartments [8]. In addition, rIZA1 appeared to be somewhat concentrated at a perinuclear region.…”
Section: Resultsmentioning
confidence: 73%
“…As shown in Fig. 5, rIZA1 was distributed diffusely in the cell, forming vesicular structures, suggesting its association with the membrane compartments [8]. In addition, rIZA1 appeared to be somewhat concentrated at a perinuclear region.…”
Section: Resultsmentioning
confidence: 73%
“…Based on an inhibitory function of preadipocyte factor 1/zona glo- merulosa-specific protein in the differentiation of preadipocytes (40) together with its expression patterns through the development of the adrenal cortex, this factor is presumed to have a role in the functional differentiation of the adrenocortical zones (42). Inner zone antigen is another candidate occurring in zFR in rat adrenal cortex that was identified to be a putative membrane progesterone receptor (43). Because antiinner zone antigen antibody inhibited activities of Cyp11b-1 in addition to steroid 21-hydroxylase in vitro (44), the factor seemed to be implicated in the steroidogenesis of zFR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, P4 can be bound by its specific membrane receptor to stimulate early intracellular signalling pathways and initiate a specific cellular response [5,8]. There are several putative membrane P4-binding proteins, including: nPRs, a novel family of membrane progestin receptors (mPRs), and progesterone receptor membrane component 1 (PGRMC1), which may form an active complex with serpine mRNA binding protein 1 (SERBP1) [5][6][7][8].It has been suggested that the nongenomic effect of P4 observed in the uterus is mediated via the 28 kDa PGRMC1 protein [5,6], which contains a short transmembrane domain and a cytochrome b5 binding domain, and is structurally different from both nPRs and mPRs [5,15]. It has been found that PGRMC1 protein is involved in steroidogenesis and cellular homeostasis [16], and also in reproductive functions like the anti-apoptotic effects of P4 in the ovary [17][18][19], or its effect on contractility of the myometrium [20].…”
mentioning
confidence: 99%